(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The article presents the parameters of the working bodies used in the preparation of seeds of repeated crops for sowing in exact quantities, with minimal processing of the combined aggregate to the top of the bush, that is, the number of discs of the rotational working body, the height of the blades installed on them crosswise, the steep pressure force exerted on the rotational Multi-factor experiments were carried out according to the Hartley-3 plan. The data obtained in the experiments were processed according to the PLANEXP program developed in the experimental-test section of the (SROIMAA) and regression equations were obtained that adequately represent the evaluation criteria. In this case, in the assessment of the uniformity of dispersion, the Cochren criterion was used, in the assessment of the value of regression coefficients, the Styudent criterion was used, and in the assessment of the adequacy of regression models, the Fisher criterion was used. The resulting regression equations were determined by the optimal values of the parameters of the soil in the zone treated by the rotational working bodies, solved together from the conditions that the level of soil motility in the treated zone is higher than 80 percent, and the traction resistance of the rotational working body is minimal.